2018
DOI: 10.3390/rs10121977
|View full text |Cite
|
Sign up to set email alerts
|

Validation of CM SAF CLARA-A2 and SARAH-E Surface Solar Radiation Datasets over China

Abstract: To achieve high-quality surface solar radiation (SSR) data for climate monitoring and analysis, the two satellite-derived monthly SSR datasets of CM SAF CLARA-A2 and SARAH-E have been validated against a homogenized ground-based dataset covering 59 stations across China for 1993–2015 and 1999–2015, respectively. The satellite products overestimate surface solar irradiance by 10.0 W m−2 in CLARA-A2 and 7.5 W m−2 in SARAH-E on average. A strong urbanization effect has been noted behind the large positive bias in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
(114 reference statements)
4
13
0
Order By: Relevance
“…The overall accuracy of the CLARA-A2 SSR data records for China is documented in Wang et al [39]. We showed that the CLARA-A2 data overestimate the surface irradiance over China on average by 10.0 W m −2 .…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The overall accuracy of the CLARA-A2 SSR data records for China is documented in Wang et al [39]. We showed that the CLARA-A2 data overestimate the surface irradiance over China on average by 10.0 W m −2 .…”
Section: Resultssupporting
confidence: 62%
“…This is also indicated by the significantly positive correlations between the CLARA-A2 minus CMA SSR biases and the changes of AOD and API shown in Table 1. In addition to this, averaged for Beijing, the AOD climatology used in CLARA-A2 with a mean of 0.19 has largely underestimated the surface-based AERONET AODs with a mean of 0.71 (Figure 8), which could explain the large overestimation of SSR by 19.2 W m −2 [39]. Therefore, aerosols mainly dominate the bias series between surface-and satellite-based SSR, which in turn, could be used to infer aerosol information and quantify aerosol-driven changes in SSR.…”
Section: A Case Study Of Beijingmentioning
confidence: 96%
See 1 more Smart Citation
“…Specifically, although the ground-based SSI data highlighted significant trends at most stations (slopes between −0.5 and 6.5 Wm −2 decade −1 ), the corresponding SARAH-2 and CLARA-A2 data did not show any significant trend: the slopes of the satellite records turned out to be in the intervals between 0.2 and 2.8 Wm 2 decade −1 and −0.4 and 3.8 Wm 2 decade −1 for SARAH-2 and CLARA-A2, respectively. The relevant role of aerosols in the comparison between satellite and ground-based SSI records has also been highlighted by Wang et al [31] for China. They reported a rather large bias for both SARAH-E (data from Meteosat East satellites) and CLARA-A2 records that largely decreased if the comparison between satellite and ground-based records was performed for rural stations only.…”
Section: Introductionmentioning
confidence: 70%
“…The biases over northeastern China might be related to the fewer sampling and higher retrieval uncertainty of surface albedo induced by longtime coverage of snow in the cold seasons [19]. The reasons for discrepancies over northwestern and southwestern China are likely due to difficulty in evaluating AOD on the variable and high-albedo surface as well as the incapable consideration of elevation impacts on the satellite algorithms and degraded data quality under snow-cover surfaces [58]. For eastern China, the difference may result from an improper representation of AOD induced by rapid economic growth in this region [58,59].…”
Section: Validation Of the Ceres Dataset Using Cma Observationsmentioning
confidence: 99%